2015
DOI: 10.1016/j.jelechem.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the double layer capacitance for electrodes in supercritical CO2/acetonitrile electrolytes

Abstract: Electrochemical impedance measurements were made in the single supercritical phase of CO 2 with 11 wt % acetonitrile as the co-solvent at temperatures and pressures between 306 and 316 K and 15.5 and 20.2 MPa over the potential range from -0.45 to +0.75 V vs. Pt. Gold, platinum and glassy carbon electrodes were studied together with the effects of electrolyte concentration for [ ], were also studied. We find that the impedance data can be described by a simple RC equivalent circuit where the uncompensated solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…These double-layer capacitances, calculated without explicit water molecules, were calculated as 18 and 22 μF/cm 2 for Au(111) and Pt(111), respectively (for further details, see the Supporting Information). This is in reasonable agreement with the experimental values that show a wide range between 10 and 40 μF/cm 2 for Au(111) and between 9 and 38 μF/cm 2 for Pt(111) and the computational result based on the application of JDFT, , where a value of 19 μF/cm 2 for Pt(111) has been reported. It should be emphasized, however, that the double-layer capacitance is highly dependent on the electrolyte in the experimental setup, where the value can differ by a factor of 2 …”
Section: Resultssupporting
confidence: 91%
“…These double-layer capacitances, calculated without explicit water molecules, were calculated as 18 and 22 μF/cm 2 for Au(111) and Pt(111), respectively (for further details, see the Supporting Information). This is in reasonable agreement with the experimental values that show a wide range between 10 and 40 μF/cm 2 for Au(111) and between 9 and 38 μF/cm 2 for Pt(111) and the computational result based on the application of JDFT, , where a value of 19 μF/cm 2 for Pt(111) has been reported. It should be emphasized, however, that the double-layer capacitance is highly dependent on the electrolyte in the experimental setup, where the value can differ by a factor of 2 …”
Section: Resultssupporting
confidence: 91%
“…Recently, Bartlett & Cook [ 61 ] published results for the study of the double-layer capacitance in scCO 2 /11 wt% MeCN mixtures of constant density between 306 K, 15.5 MPa and 316 K, 20.2 MPa. They found that the results for Pt and Au electrodes could be described by a simple Helmholtz layer model.…”
Section: Supercritical Fluids As Solvents For Electrochemistrymentioning
confidence: 99%
“…Black squares: 0.5 mm diameter platinum disc; red circles: 0.5 mm diameter gold disc; blue triangles: 1 mm diameter glassy carbon disc [61]. (Reproduced with permission from [61]. Copyright c Elsevier.…”
Section: (C) the Double Layer In Supercritical Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports exist concerning the solubility of inorganic salts and small organic molecules in scCO 2 , the conductivity of scCO 2 and applicable electrolyte additives, ,, voltammetric experiments on ferrocene and decamethylferrocene, , and electrochemical metal depositions in scCO 2 . Nevertheless, only a few reports have so far addressed the electrochemical reduction of scCO 2 itself under such conditions. , Thus, a deeper understanding of the performance gain using scCO 2 for the CO 2 R is yet to be established.…”
Section: Introductionmentioning
confidence: 99%